Eumlat Maediniat fi Suriat 1946 - 1948 (Journal of the College of Basic Education, 2026)
Syria entered a new phase in political and economic life. With the departure of the occupying forces, various political and social currents became active, and the labor movement had a large share in the activity. This period witnessed the emergence of the labor movement as a social and political force to defend their rights and improve their economic conditions left by the occupation. This period was characterized by the large number of strikes and labor protests demanding an improvement in the economic level, and this was a cornerstone in the history of the labor movement in Syria, as the labor movement succeeded in conveying their voice to the House of Representatives to demand their economic rights.